Reformulating the entropic contribution in molecular docking scoring functions. Issue 19 (27th May 2016) - Procacci, Piero
Abstract : We have derived, in the context of the Rigid Rotor Harmonic Approximation (RRHO), a general mass and Planck's constant h independent expression for the dissociation free energy in ligand–receptor systems, featuring a systematically (anti‐binding) additive negative entropic term depending on readily available ligand–receptor quantities. The proposed RRHO expression allows to straightforwardly compute the absolute standard dissociation free energy without resorting to expensive normal mode analysis or other dynamical matrix‐based techniques for evaluating the entropic contribution, hence providing an effective scoring function for assessing docking poses with no adjustable parameters. Our RRHO formula was tested on a set of 55 ligand–receptor systems obtaining correlation coefficients and unsigned mean errors comparable to or better than those obtained with computationally demanding techniques for the dissociation entropy assessment. The proposed compact reformulation of the RRHO entropy term could constitute the basis for new and more effective scoring functions in molecular docking‐based high‐throughput virtual screening for drug discovery. © 2016 Wiley Periodicals, Inc. Abstract : In this contribution, in the context of the Rigid Rotor Harmonic Approximation (RRHO), a general mass and Planck's constant independent expression for the dissociation free energy in ligand–receptor systems is derived. The proposed RRHO expression features a systematically additive negative (anti‐binding) entropic term depending on readily available ligand–receptor quantities, allowing to straightforwardly compute the standard dissociation free energy without resorting to expensive normal mode analysis or molecular dynamics‐based approaches.